The corner kick in football: Coordinating to success - Vicente, A.; Fernando, C.; Lopes, H. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In the FIFA World Cup 2010 there was an average of 28.28 shots per game (14.14 per team), but only 10.67 shots on goal (5.34 per team). There was an average of 9.80 corner kicks per game (4.9 per team). It is clear that the corner kick is a very important opportunity to score. The corner kick is a relation between the shooter, his team partners and the opposite team players (Almada et al., 2010). The aim of the present study was to analyse the dynamics of corner kicks situations in order to understand how a top raking team acts in a very important competition. Methods We know from a model of football corners (Almada et al., 2010) that the advantage of the attacking team comes from the anticipation they take from the defending team. We`ve analyzed all 14 corner kicks from the FIFA World Cup 2010 Final (Netherlands-6 vs. Spain-8). Using video analysis software (Kinovea-0.8.7) we`ve analyzed how many attacking players where in a position to score when the ball arrived in front of the goal and how many players tried to reach the place where that specific ball could be scored and if theteam mates where trying to help them. Results & Discussion No goal was scored from this situation. The attacking team could be in advantage if they prepared the right strategy. We analyzed if there was an attacking player in the place reached by the ball or a little sooner (500 milliseconds) (in all 14 corner kicks only 5 players where), how many team mates where trying to help the action of these player (in 11 situations there where attacking players near but from these 8 tried to score to and the others 9 had no action that we could classify as positive) and how many others groups of attacking players where doing similar actions in other places so that they could be trying a deceptive action to attract defending players (only 4 groups could be classified as having an intentional group movement, but from these only 1 took defending players from the place where the ball had reached). Conclusion There are a considerable number of corner kick situations in a football match that if properly prepared by the attacking team can increase the chances of scoring. It is possible to previously define a strategy preparing the attacking players to, knowing where the ball will fall, make intenional actions to get advantage over the defenders preparing the opportunity widow for the striker to score. Coordination between the corner taker, the attacking team and the player who will try to score is crucial for success.